Teachers' Speech Acts in Teaching English on the Third Year at SMP Negeri 29 Padang - Hanna Fadilla Rusdi; Nofrina Eka Putri (Universitas Negeri Padang, 2022)
This study aims to find out the types of speech acts and illocutionary acts used by English teachers during teaching and learning process. This study employed descriptive qualitative research. The participants of this research were five English teachers. The sample was chosen using the purposive sampling technique. The criterion for choosing the sample was the teachers who teach English on the third year at SMPN 29 Padang. The instrumentations of this research were observation sheet and video recording. The study used Searle’s theory to analyze the data. The findings shows that there were four types of illocutionary acts performed by the teachers. There were representatives, directives, expressives, and commissives. The teachers used 92 utterances. From 92 utterances, directives discovered to be the most uttered speech acts which occurred 52 times (56,52%), representatives were used 33 times (35,87%), expressives were used 7 times (7,61%), and commissives appeared to be the least speech acts used by the teachers which only occurred in 1 utterance (1,09%). The use of directive speech acts apparently allow them to understand what the teachers’ meant during teaching and learning activities.